Enhancing conceptualisations of information behaviour contexts through insights from research on e-dictionaries and e-lexicography - Theo JD Bothma; Ina Fourie (Information Research: An International Electronic Journal)
Introduction. Extensive conceptualisations of context in information behaviour research do not extend to all contexts revealed in the use of electronic (e)-dictionary and similar e-sources. Information behaviour emphasises users’ contexts and their situations. As intermediaries, examples of using e-dictionaries reveal additional contexts. E-dictionary research and lexicographical insight add additional conceptualisations of information behaviour contexts.